Association between obesity and asthma among teenagers - Bertolace, Maria do Pilar Carneiro (2008)
CONTEXT AND OBJECTIVE: Obesity and asthma are serious and growing problems. Since adipose tissue produces infl ammatory substances, the aim of this study was to estimate the prevalence of asthma among students at schools in São José do Rio Preto (Phase 1), and to corroborate the hypothesis for an association between obesity and asthma among these students (Phase 2). DESIGN AND SETTING: Cross-sectional study at Faculdade de Medicina de São José do Rio Preto (Famerp). METHODS: The study consisted of two successive and dependent stages. Phase I was a cross-sectional study on 4103 randomly selected students (13-14 years old), to determine the prevalence and severity of asthma. Phase II was an analytical cross-sectional study on 431 students (190 asthmatics and 231 non-asthmatics) from Phase I, to evaluate the hypothesis of an association between obesity measured by the body mass index (BMI) and asthma. To diagnose asthma and obesity, the criteria of the International Study of Asthma and Allergies in Childhood (ISAAC) and the chart from the Centers for Disease Control (CDC; 2000) were used. The data were analyzed using Student’s t test. RESULTS: We found that 5.6% of the students analyzed in Phase I were asthmatic. The BMI among the asthmatic students (21.84 kg/m2) was higher than the BMI among the nonasthmatics (21.73 kg/m2), although the p value was 0.766. CONCLUSION: In our study group, we did not fi nd any association between increased BMI and the prevalence of asthma.